2020
DOI: 10.1186/s43088-020-00088-2
|View full text |Cite
|
Sign up to set email alerts
|

Psidium guajava leaves assisted green synthesis of metallic nanoparticles: a review

Abstract: Background Several attempts have been made for green synthesis of metallic nanoparticles, revealing the significance of plant extracts in reducing metal source to nanoparticles and applications in various domains of science. Main body Psidium guajava (guava) is evergreen, edible fruit-bearing plant, belonging to family Myrtaceae. Its leaves are reported to contain several phytochemicals like tannins, glycosides, terpenes, and triterpenes. This article focus on applications of Psidium guajava leaves extract in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…It has been observed that plant extract can be used for the green synthesis of metallic nanoparticles depending on the reducing properties of this extract 43 . In the present study, AgNPs were prepared using PGLE.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that plant extract can be used for the green synthesis of metallic nanoparticles depending on the reducing properties of this extract 43 . In the present study, AgNPs were prepared using PGLE.…”
Section: Discussionmentioning
confidence: 99%
“…The leaves of plants grow in pairs and opposite to each other, elliptic to oblong, 5-15 cm long x 3-7 cm broad. The leaf is pubescent and veined in the lower part and glabrous in the upper part 16 .…”
Section: Cultivation and Collectionmentioning
confidence: 99%
“…Plants element likes bulks, roots, fruits and leaves are used typically to synthesize NPs. 10 Moreover, extract of green leaves of various medicinal plants are used as they have significant reducing and capping agents to convert metallic ions to form NPs. Azadirachta indica (neem), Moringa oleifera , Justicia adhatoda , 11 Aloe vera and Psidium guajava ( P. guajava ) etc.…”
Section: Introductionmentioning
confidence: 99%
“…P. guajava leaf extract contains biochemicals such as polyphenols, carotenoids, terpenoids, flavonoids, tannins and triterpenes could be responsible for the reduction of metal ions to NPs. 9,10 Bose et al prepared AgNPs using P. guajava and investigate their anti-bacterial activity against Gram negative bacterial strain. 9 Sharmila et al 17 demonstrates result for both Gram-negative and Gram-positive bacteria with zone of inhibition less than 10 mm.…”
Section: Introductionmentioning
confidence: 99%